Data on Digital Transformation in the German Socio-Economic Panel - Fedorets, Alexandra; Kirchner, Stefan; Adriaans, Jule; Giering, Oliver (Jahrbücher für Nationalökonomie und Statistik, 2022)
Public debates and current research on "digitalization"suggest that digital technologies could profoundly transform the world of work. While broad claims are common in these debates, empirical evidence remains scarce. This calls for reliable data for empirical research and evidence-based policymaking. We implemented a data module in the Socio-Economic Panel to gather information on digitalization in three domains: Artificial intelligence (AI), platform work, and digitalized workplace. This paper describes the existing approaches to measure technological exposure, the challenges in operationalization of digital transformation in a household survey, the implemented questionnaire items, and the research potential of this new data.
CRIS-Team Scopus Importer:2025-04-09
Keywords: artificial intelligence; digital workplace; household survey; operationalization; platform work